Assessment of Factors Responsible For Barbers’ Adherence with Health and Safety Provisions in Tamale Metropolis, Ghana - Isaac Wuptiga Jatuat, Issah Eliasu; Dawuni, Mohammed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Adherence to therapies is a primary determinant of treatment success. Failure to adherence is a serious problem whichnot only affects the patient but also threatens the commercial success of a profession. The paper assesses factorsresponsible for barbers’ adherence with health and safety provisions in Tamale Metropolis, Ghana. The study adopted acase study approach. Accidental sampling technique was used to draw sample from the barbering population, withquestionnaire as the main data collection instrument. Total of 70 retrieved questionnaires gave 77.8% response rate.Descriptive statistics including percentages mean and standard deviation was used to analyze the data, while inferentialstatistics namely regression used to determine the relationship between the variables. Results revealed that sixindependent variables showed statistically significant relationship with compliance with safety and health provisions.Findings also showed that the insistence of clients of the existence of health and safety measures is highest contributor tobarber compliance with health and safety provisions. it is was recommended that a risk assessment audit be carriedacross barbering salons, so that information gathered would pave way for training. This allowed employees to acquiregreater competencies to manage their work, leading to enhancement of their occupational health and safety in TamaleMetropolis.